(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article examines the distinctive features of management science in nursing and explores the essence of management competencies within the healthcare system. In modern healthcare, the role of nurses is closely linked not only to patient care but also to managerial and organizational responsibilities. Therefore, the study of management science in nursing, the development of leadership skills, and the formation of professional competencies are of significant importance. The article analyzes the core functions of nursing management, the specific characteristics of the management process in nursing practice, and the key management competencies required of contemporary nurse leaders. The findings highlight the crucial role of management knowledge in ensuring effective healthcare delivery and improving the quality of medical services.